Interactions of Plasmodium blood and liver stages within a single host - Portugal, Sílvia Vilar, 1980- (2010)
Tese de doutoramento, Ciências Biomédicas (Ciências Biopatológicas), Universidade de Lisboa, Faculdade de Medicina, 2010